TANMALACCA (VIEWS OFEDUCATION1897-1949and thoughts) - Nurwaryanti ' '; Ridwan Melay Ridwan Melay; Marwoto Saiman Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Education is an important asset in the life of a society or a nation. Education is the gateway to the changes to be free from the shackles of ignorance, so that it can achieve an independent human being. Freedom from poverty, and ignorance, so that it can become an independent nation in social, economic, political, legal, and cultural. The development of education in Indonesia that progress can not be separated from the role of leaders and scholars who have contributed much thoughts and ideas of the diamond to education. One of the figures who took part in education is Tan Malaka. Tan Malaka background of a teacher and a revolutionary fighter offers an educational concept that is popular. The purpose of this study was to determine the life history of Tan Malaka, to know the views and thoughts of Tan Malaka in the field of education, to know the struggles of Tan Malaka in education and the obstacles faced by Tan Malaka in the fight for education. The research method used is the historical and descriptive methods. The aim is to reconstruct, analyze, evaluate, and explanation of evidence - evidence to get the facts reach conclusions that can be justified. The results showed that the concept of popular education Tan Malaka is based on the people, democracy and an attempt to liberate the people of Indonesia from the Dutch colonization. Educating students to think realistic, critical, dynamic, and logical, so can easily face the challenges of achieving independence era. Teach organization to establish a strong and confident personality in every way. Giving students the freedom to determine the attitudes, choices and take responsibility for his choice. Education for always berorintasi down means educating students to love the poor and work.Keywords : Tan Malaka, Views and Thoughts, Education